2021
DOI: 10.1007/s10552-021-01392-7
|View full text |Cite
|
Sign up to set email alerts
|

What mediates the racial/ethnic disparity in psychosocial stress among breast cancer patients?

Abstract: Background Prior studies have observed greater levels of psychosocial stress (PSS) among non-Hispanic (nH) African American and Hispanic women when compared to nH White patients after a breast cancer diagnosis. We aimed to determine the independent and interdependent roles of socioeconomic position (SEP) and unmet support in the racial disparity in PSS among breast cancer patients. Methods Participants were recruited from the Breast Cancer Care in Chicago … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Another important finding is that NHB and NHO/Hispanic survivors with both frequent poor mental and physical health were 95% less likely to receive guideline-concordant CRC screening. This finding was consistent with prior literature, [42][43][44][45][46] with lower screening use possibly explained by poor physical and/or mental health. In breast cancer, Bowen et al 42 found that NHB and NHO survivors were more likely to report lower score in physical health domain.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another important finding is that NHB and NHO/Hispanic survivors with both frequent poor mental and physical health were 95% less likely to receive guideline-concordant CRC screening. This finding was consistent with prior literature, [42][43][44][45][46] with lower screening use possibly explained by poor physical and/or mental health. In breast cancer, Bowen et al 42 found that NHB and NHO survivors were more likely to report lower score in physical health domain.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, greater psychosocial stress, which may influence physical health outcomes through psychological mechanisms, was also observed in these two racial/ethnic groups because of socioeconomic disparities in breast cancer. 45 Furthermore, Black prostate cancer survivors with bowel and bladder incontinence were more likely to screen positive for depression symptoms. 43 Together, racial/ethnic differences and the influence of mental and physical health in breast and prostate cancers play important roles in survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…First, the majority of participants in the included studies were White and female, which does not reflect the broader patient population with cancer, including non-White ethno-racial groups (ie, African American or Black, American Indian and Alaska Native, Asian, Native Hawaiian or other Pacific Islander, and Hispanic or Latino populations). It is well documented in the literature that the impact of cancer on psychological distress and quality of life is worse for racial and ethnic minority groups [ 100 - 102 ]. Therefore, future trials should include more participants from underrepresented groups to reduce health care disparities and improve generalizability in diverse populations [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Those who do survive are at greater risk for inferior physical and mental health outcomes compared with their White peers. [2][3][4] Specifically, Black, Hispanic, and Indigenous survivors experience poorer physical and mental health outcomes, such as increased late effects of cancer treatment, [5][6][7] impairment in activities of daily life, 8 sleep, 9 psychosocial stress, 3 and health-related quality of life. [10][11][12][13] Notably, these adverse outcomes are in the context of a greater burden of mental and physical health challenges survivors of cancer face in comparison to their noncancer-exposed peers.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals from historically marginalized racial and ethnic groups diagnosed with cancer are less likely to survive than their White counterparts 1 . Those who do survive are at greater risk for inferior physical and mental health outcomes compared with their White peers 2–4 . Specifically, Black, Hispanic, and Indigenous survivors experience poorer physical and mental health outcomes, such as increased late effects of cancer treatment, 5–7 impairment in activities of daily life, 8 sleep, 9 psychosocial stress, 3 and health‐related quality of life 10–13 .…”
Section: Introductionmentioning
confidence: 99%